Phenomenological Study of Parents' Role in Caring for Children's Dental and Oral Health at Jelegong Elementary School - Azzahra, Resa Safa; Andriani, Ria; Martini, Eva (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Dental and oral health is very influential for children's lives in schoolage children, it is a very serious thing to think about because several dental health problems in children are still a problem around the world. Poor dental care can cause problems with teeth and mouth such as canker sores, bad breath, gingivitis and tooth caries. Parents have a major role in educating, guiding, and caring because parents are closest to their children as an important factor in preventing tooth and mouth decay. Riskesdes 2018 reported the prevalence of health disorders of damaged teeth/caries/dirty teeth in children 80-90%, children aged 3-4 years as much as 81.1%, ages 5-9 years as much as 92.6% and ages 10-14 as much as 73.4%. This study aims to describe the understanding of the role of parents about children's dental and oral health at SDN Jelegong. The research method uses a phenomenological qualitative research design with 6 participants selected purposively. Data collection was carried out in November to December 2024 through indepth interviews, observations, and documentation. Documentation using an Iphone 7+ camera and a Redmi 12 android voice recorder. The results of the research were obtained in 3 themes including: 1) Teaching children's dental and oral care, 2) Children's dental and oral health knowledge, 3) Obstacles in caring for children's dental and oral health. It is hoped that parents should be able to improve their role well in maintaining dental and oral health in schoolage children because at that age children need the role of parents so that they do not experience problems with teeth, one of which is dental caries.